2016
DOI: 10.21037/jtd.2016.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Tumor heterogeneity on 18F-FDG-PET/CT for response monitoring in non-small cell lung cancer treated with erlotinib

Abstract: Response monitoring using fluorodeoxyglucose positron emission tomography acquired together with low dose computed tomography (FDG-PET/CT) textural features has potential in targeted treatment with erlotinib in non-small cell lung cancer (NSCLC) patients. Patients with substantial decrease of metabolic activity during erlotinib treatment will probably benefit from continued treatment. However, various aspects of the method (quantification tools, cut-off values, etc.) need to be standardized before the software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…18 F-FDG PET has shown some value in EGFR-mutated lung adenocarcinoma, and several studies have shown that image features extracted from 18 F-FDG PET are associated with EGFR mutation status [34][35][36]. In addition, 18 F-FDG PET derived radiomic features have been shown to anticipate the treatment response to TKIs in EGFR-mutated lung cancer [37][38][39][40][41]. However, the prognostic value of 18 F-FDG PET-based radiomic features for the survival of lung cancer patients treated by EGFR-targeting TKIs has not been well investigated.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET has shown some value in EGFR-mutated lung adenocarcinoma, and several studies have shown that image features extracted from 18 F-FDG PET are associated with EGFR mutation status [34][35][36]. In addition, 18 F-FDG PET derived radiomic features have been shown to anticipate the treatment response to TKIs in EGFR-mutated lung cancer [37][38][39][40][41]. However, the prognostic value of 18 F-FDG PET-based radiomic features for the survival of lung cancer patients treated by EGFR-targeting TKIs has not been well investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, FDG-PET/CT has a fundamental limitation as a tailored predictive modality since its image reflects various tissue reactions which could weaken a representative value of our textural parameters. [ 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, active mutations in EGFR could activate relevant intracellular signaling pathways to enhance tumor glycolysis; consequently, intense 18 F-FDG uptake manifestation in PET images was observed (15). Previous studies conducted by other groups have also demonstrated a positive correlation between the oncogene mutational status and the maximum standardized uptake value (SUVmax) in PET images (1618). Nevertheless, there have been conflicting results (19).…”
Section: Introductionmentioning
confidence: 86%